Intraregional and inter‐regional variability of herbicide sensitivity in common arable weed populations. (15th April 2015) - de Mol, F; Gerowitt, B; Kaczmarek, S; Matysiak, K; Sønderskov, M; Mathiassen, S K; Zwerger, Peter
Summary The question on intraregional versus inter‐regional variability in herbicide sensitivity for weed populations is of major importance, both in extrapolation of model parameters and in herbicide zonal approval procedures. We hypothesised that inter‐regional variability in herbicide sensitivity for field populations would be the same as intraregional variability for regions with similar climatic conditions. Seeds of field weed populations were collected in a Danish, German and Polish region. Herbicide sensitivity was tested in dose–response experiments in the glasshouse with flufenacet and iodosulfuron (Apera spica‐venti), florasulam and tribenuron (Tripleurospermum inodorum), diflufenican, diflufenican + flurtamone and pendimethalin (Viola arvensis). ED50 values and variance components of the ED50 values were estimated to describe the influence of region, year and population. The regions accounted for a maximum of 26% of the variance and always less than the variance accounted for by individual populations. Sensitivity indices (SI50) were calculated as the ratio between ED50 of the test population and a reference population. There was considerable intraregional variability in SI50 values and SI50 values from a single region did not consistently differ from other regions. The large intraregional variability in herbicide sensitivity between populations, with no evidence of resistance, is of interest both for zonal evaluation of herbicides and resistance research. For practical weed management, we conclude that dose–response functions can be transferred between the study regions, for example for the common use in decision support systems with proper insurance for the control of less sensitive populations.